2017
DOI: 10.5194/acp-17-11135-2017
|View full text |Cite
|
Sign up to set email alerts
|

Variability and quasi-decadal changes in the methane budget over the period 2000–2012

Abstract: Abstract. Following the recent Global Carbon Project (GCP) synthesis of the decadal methane (CH 4 ) budget over 2000, we analyse here the same dataset with a focus on quasi-decadal and inter-annual variability in CH 4 emissions. The GCP dataset integrates results from topdown studies (exploiting atmospheric observations within an atmospheric inverse-modelling framework) and bottom-up models (including process-based models for estimating land surface emissions and atmospheric chemistry), inventories of anthropo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
159
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(173 citation statements)
references
References 123 publications
13
159
1
Order By: Relevance
“…), reaching 1,820 ppb by 2012, with an increase rate of 5.2 ± 0.2 ppb/yr during 2008–2012 (mean ± SD; Saunois et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), reaching 1,820 ppb by 2012, with an increase rate of 5.2 ± 0.2 ppb/yr during 2008–2012 (mean ± SD; Saunois et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of global CH 4 fluxes (35 Tg/yr) have been attributed to emissions from high-latitude wetlands north of 50°N (Sebacher et al 1985, Matthews and Fung 1987, Crill et al 1988, Fung et al 1991, Zhuang et al 2004, Thornton et al 2016. Emissions from natural wetlands are thought to be partially responsible for the recent rise in global CH 4 concentration (Kirschke et al 2013), reaching 1,820 ppb by 2012, with an increase rate of 5.2 AE 0.2 ppb/yr during 2008-2012 (mean AE SD; Saunois et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript, the ensemble of top‐down studies provided by eight global inverse systems suggested a dominant contribution to the global emission increase from agriculture and waste (+10 [7–12] Tg CH 4 yr −1 ), wetlands (+6 [−4–16] Tg CH 4 yr −1 ), and fossil fuel‐related emissions (+7 [−2–16] Tg CH 4 yr −1 ) from 2000–2006 to 2008–2012. Saunois et al () also showed that the decrease of biomass burning emissions (−3 [−7–0] Tg CH 4 yr −1 ) could be consistent with the carbon isotopic signature. The uncertainties of these mean emission changes are, however, very significant as shown by the range inferred by eight inversions.…”
Section: Introductionmentioning
confidence: 99%
“…Methane then began to rise again around 2006. AGAGE data and emission estimates for methane have appeared in multiple recent papers Kirschke et al, 2013;Loh et al, 2015;Patra et al, 2011;Thompson et al, 2015;Saunois et al, 2016Saunois et al, , 2017. Nitrous oxide is the third most important long-lived greenhouse gas (after CO 2 and CH 4 ) and the major source of ozone-depleting nitric oxide (NO) and nitrogen dioxide (NO 2 ) in the stratosphere (Ravishankara et al, 2009 Huang et al (2008), Nevison et al (2011), Thompson et al (2013, b, c), and Saikawa et al (2014a using AGAGE and NOAA-ESRL data.…”
Section: Trends In Kyoto Protocol Gasesmentioning
confidence: 99%